Tolerance Index and Policy Model in Sustainable Tourism Development in Central Lombok Regency, Indonesia - Agus, Agus; Ansori, Zakaria (MUHARRIK: Jurnal Dakwah dan Sosial, 2023)
This article aims to describe the tolerance index and management model of tourism development in Central Lombok Regency. Using the mix-method, this study found that the religious tolerance index information was 3.61 or had a high category. The religious tolerance index is supported by a two-dimensional-based management model, namely regulation and institutional. The regulatory dimension refers to the 2006 Joint Regulation of the Minister of Religion and the Minister of Home Affairs, the 2020-2024 Ministry of Religion Strategic Plan, and the 2021-2026 Lombok Regency RPJMD. Recommended policy development models include; The regulatory dimension is guided by Presidential Regulation Number 58 of 2023, Regulation of the Minister of Religion Number 3 of 2024, and the Central Lombok Regency RPJPD 2025-2045. By referring to these regulations, the institution of tolerance management policy applies the hexa-helix model collaborative management approach, namely policies through the collaboration of six stakeholders which include: local governments; FKUB; the business world; NGOs / religious organizations; mass media; and universities. Local governments play a role in designing and developing policies, while other stakeholders play a supporting role in policy management.